Human Genetics and the Causal Role of Lipoprotein(a) for Various Diseases - Kronenberg, Florian (Cardiovasc Drugs Ther, 2016)
Lipoprotein(a) [Lp(a)] is a highly atherogenic lipoprotein that is under strong genetic control by the LPA gene locus. Genetic variants including a highly polymorphic copy number variation of the so called kringle IV repeats at this locus have a pronounced influence on Lp(a) concentrations. High concentrations of Lp(a) as well as genetic variants which are associated with high Lp(a) concentrations are both associated with cardiovascular disease which very strongly supports causality between Lp(a) concetrations and cardiovascular disease. This method of using a genetic variant that has a pronounced influence on a biomarker to support causality with an outcome is called Mendelian randomization approach and was applied for the first time two decades ago with data from Lp(a) and cardiovascular disease. This approach was also used to demonstrate a causal association between high Lp(a) concentrations and aortic valve stenosis, between low concentrations and type-2 diabetes mellitus and to exclude a causal association between Lp(a) concentrations and venous thrombosis. Considering the high frequency of these genetic variants in the population makes Lp(a) the strongest genetic risk factor for cardiovascular disease identified so far. Promising drugs that lower Lp(a) are on the horizon but their efficacy in terms of reducing clinical outcomes still has to be shown.